The Influence of Labor and Population Growth on Economic Growth in Indonesia the Year 2017 – 2022 - Yoga SWASTIKA; Ketut DHARMA; Lanang Putu TANTRA (Loka: Journal Of Environmental Sciences, 2023)
Purpose:This research aims to complement the shortcomings of previous research, which discusses differences in views regarding the impact of Labor and Population Growth on Economic Growth. This research focuses on the population experiencing unemployment as a labor and population growth marker, which influences economic growth in Indonesia. The research aims to understand the impact of Labor and Population Growth on Economic Growth in Indonesia over six years, namely from 2017 to 2022.Methodology:The research method used is panel data regression, which involves collecting data regarding labor, population growth and economic growth from 2017 to 2022 via internet sources.Findings:The research results, using panel data regression analysis and hypothesis testing (t-test and R2 determination test), show that the labor variable (X1) is not significant and hurts economic growth (Y) in the 2017 – 2022 period, while the population growth variable (X2) has a significant and negative effect on economic growth (Y) in the same period.Implication:The labor variable (X1) is stated to have a negative and insignificant influence on economic growth (Y) in 2017 - 2022. The population growth variable (X2) is stated to have a significant and negative influence on economic growth (Y) in 2017 - 2022.